Life cycle assessment for managing household waste in Tehran, Iran - Heravi, Helen Morabi (2014)
Life cycle assessment (LCA) methodology in this thesis was used to determine the optimum Recyclable Household Waste management strategy for Tehran city. The thesis targets the household waste of Tehran, and the problem was made by posing significant environmental, health hazards, and harming economies. The municipality intends to eliminate activities that have the potential to cause a non-compliance till prevent recurrence. Corrective actions have an effect on the potential problems which is a crucial issue for any major cities worldwide. Tehran is a large urban cluster, which is chosen for this study. The study also fits with the five year waste management, design of the municipality. Life cycle management (LCM) of household waste is analyzed based on direct data observations. The current research has relevance in solving real life environmental problems. The main aim of the study was examined and recommends ways to reduce the environmental emissions of recyclable household waste operations. The goal of study to assess the environmental potential effects such, acidification; global warming, eutrophication, solid waste and water consumption per capita of household waste in the steps of storing, collecting and recycling by IMPACT2000+ Method. Type study is cradle to cradle of the LCA method. The main objective of this thesis is studying the achievement to optimum potential environmental impacts per 200 kg capita in managing household waste. The specific objectives are the identification of the most environmentally aspects (EMS), to assess the risk of the unit processes of household waste, to analyze the inventory of unit processes, to determine the correlation between inputs and out-puts also determine the sensitivity value outputs to inputs in the life cycle, to assess potential environmental emissions and environmental impacts of three group scenario in the life cycle and, to determine of the best scenario for Tehran. The objectives focus on related sustainable development and environment issues and the current status of different environmental tools. Database emissions were estimated by the World Health Organization (WHO) and Japan International Cooperation Agency (JICA). Life Cycle Assessment (LCI) provides the basis for evaluating the potential environmental impacts. The thesis adopts a unique combination of analytical and field based methods. The key component is direct observations and field data collections, which is strengthened by different analysis and models. An analysis is made based on observed data and models. Both direct and indirect emissions associated with source separation practices as well as those avoided due to replacing storage bag/bin and vehicles. The categories of environmental and resource consumption that is proportional to the local and global level, mainly includes the effects of acidification, global warming, respiratory effect, solid waste and water consumption. System boundary recyclable materials are as cradle to cradle and the separation and storage of recyclable materials has been started from homes, kerbside or buy back centers and ultimately lead to recycling factories. Functional unit is calculated based on the capita of collecting recyclable materials. Collection and storage of various types of recyclable materials used different equipment. Due to time and resource constraints, this LCA evaluates the potential impacts storage bags and vehicle collection in the recyclable household waste, a 57% door-to-door service, 34% kerbside sorting, and 9% buyback centers by work sheets. An effective source separation management system is needed in Tehran since the generated recyclable materials are separated in the kerbside without any control and hasn’t had a materials recovery facility (MRF)/Transfer Stations (TS). Waste (MSW) produced in Tehran was 7,000 metric tons per day. Currently, Tehran produces more than 2.5 million tonnes of waste every year. Waste analysis was carried out in all of the 22 Tehran regions, the results shows that 32% of waste is recyclable. Waste source separation promotes the use of reachable waste and reduce environmental and health risks as well as the national capital. Several waste source separation schemes were implemented in Tehran regions, including: Tehran waste management organization currently promote and support initiative waste source separation programs of the buyback center, door-to-door service and kerbside sorting. Most local authorities have practiced forms of reclamation in past years. Source separation schemes were established in 1995 by contractors that currently covenant its surplus to participating local and government contractors in developing their long-term strategy. These containers are located in various places around the main city of the region – Tehran. There are 22 regions where people can bring their pre-separated recyclable materials. The collected materials, in principle, are going to be sold to recycling companies and then to the market. In this thesis source separation alternative were investigating an environmental impact and process risk. Waste source separation is concluded that there is a high risk of recycling due to lack of quality control of the product. The thesis concludes with a series of actions for municipal waste management. With detailed literature review, original data analysis, and has been able to provide in-depth analysis of the research problem and has provided recommendations. The alternative scenarios were compared through the IMPACT 2000+Method (Excel file of Gabi software; ver 2.1) and these comparisons were carried out from the global warming, human respiratory, acidification, eutrophication, water consumption, and solid waste points of view. In total, nine different scenarios were developed as alternatives on management system of the recyclable household and hotspot analysis is made considering its environmental impacts. Impacts on respiration, BOD, Total N, acidification, global warming is calculated based on these nine scenarios. Storage, collection of recyclable materials and recycling processes were considered in these scenarios. According to the comparisons, sensitive analysis and emission burden model, in all nine scenarios, total emissions are consistently lower when plastic bag is used rather than paper bags. To perform each of the suggested scenarios will depend on the decision policies. It is recommended developing a kerbside with High Density Polystyrene (HDPE) blue bins and exciting buy back centers programs in the near future. A kerbside system by HDPE blue bin by using mini-truck is the more environmentally preferable alternative and process has lower risk. Recommendation, used on mini-truck and kerbside collection are the most commonly used source separation systems, that are perform in worldwide.